Tuberous Sclerosis Complex Associated with Papillary Serous Carcinoma of the Peritoneum, Lymphangioleiomyomatosis, and Angiomyolipoma. (19th October 2011) - Wakamiya, Tomihiro; Sugita, Yasuo; Hashiguchi, Mariko; Iwasaka, Tsuyoshi; Tokunaga, Osamu
Abstract : Tuberous sclerosis complex (TSC) is associated with benign and malignant tumors, including lymphangioleiomyomatosis (LAM) and angiomyolipoma (AML). We herein describe the TSC case of a 50-year-old woman having a papillary serous carcinoma of the peritoneum (PSCP), LAM, and AML. On microscopic examination, the PSCP cells showed a cuboidal to columnar shape, proliferated into the papillae, and infiltrated into the peritoneal cavity and anterior thoracic wall. On immunohistochemical evaluation, the tumor cells were positive for epithelial membrane antigen, human epidermal cytokeratins, and progesterone receptor, but negative for calretinin, carcinoembryonic antigen, MCF-7 cell line (Ber-EP4), and estrogen receptor.